Have Indonesian Rubber Processors Formed a Cartel? Analysis of Intertemporal Marketing Margin Manipulation - Thomas Kopp; Zulkifli Alamsyah; Raja Sharah Fatricia; Bernhard Brümmer (GOEDOC, Dokumenten- und Publikationsserver der Georg-August-Universität, 2014)
In Indonesia the agricultural sector plays a key role for broad based economic development in rural areas. Rubber is one of the most important crops, and Indonesia is the second largest producer in the world. However, a high level of concentration in the processing industry limits the spread of the incoming wealth. In Jambi province on Sumatra, the strong market power of the crumb rubber factories is based on cartelization. This has tremendously negative welfare effects on the rural population, effects which are also likely to be relevant for many other provinces throughout Indonesia. For the society in general and policy makers specifically, it is essential to know about the extent of the whole issue. Thus we study the price transmission at these factories and assess their true market power. We make use of the non-parametric estimation technique of penalized splines in order to understand the error correcting process without having to make a priori assumptions about it. We then estimate an Auto-Regressive Asymmetric Threshold Error Correction Model to quantify both the extent of the threshold effect as well as the rents that are redistributed from the farmers to the factories. The analysis is based on daily price information from a period of four years (2009-2012). To the best of our knowledge, this is the first paper to quantify the additional distributional consequences of intertemporal marketing margin manipulation based on cartelistic market power.
urn:nbn:de:gbv:7-webdoc-3908-9
Keywords: 330; intertemporal marketing margin manipulation; rubber cartel; Indonesia; asymmetric price transmission; threshold co-integration; Gummiindustrie; Kartell; Preiswettbewerb; Marktmacht; Kointegration; Schätzung; Indonesien